Studies on rapid multiplication of black pepper (Piper nigrum L.) on soil mound - G D Joshi, D S Bagade, D B Malve, N R, R G Khandekar, P M Haldankar, V S Pande; Ramana, Bhagwat, A D Rangwala, N D Jambhale, K V (Journal of Spices and Aromatic Crops, 2004)
An experiment was conducted to study rapid multiplication of black pepper (Piper nigrum) on soil mound at Dapoli (Maharashtra). The black pepper plants were planted at the base of soil mound (2.5 m width, 0.60 m height at centre, 18 m length, 45’ angle slope) at various spacings (15.0,22.5, 30.0 and 37.5 cm) and compared with cuttings raised by bamboo and traditional methods. The vines in soil mound method exhibited superior performance with respect to length and root production node". The availability of cuttings from soil mound method was also the highest. The rooting percentage of cuttings obtained from soil mound and bamboo methods were significantly superior over traditional method of propagation. The B : C ratio for marketable black pepper cuttings by soil mound method was the best (2.1:1.0). Planting base material at 15 cm spacing on soil mound was the best and produced more runners per unit area as compared to other spacing treatments and traditional method.